2020
DOI: 10.1126/sciadv.aay5195
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon quantum interference and entanglement at 2.1 μm

Abstract: Quantum-enhanced optical systems operating within the 2 μm spectral region have the potential to revolutionise emerging applications in communications, sensing and metrology. However, to date, sources of entangled photons have been realised mainly in the near-infrared 700-1550 nm spectral window. Here, using custom-designed lithium niobate crystals for spontaneous parametric down-conversion and tailored superconducting-nanowire single-photon detectors, we demonstrate two-photon interference and polarisation-en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 54 publications
(63 reference statements)
0
58
0
Order By: Relevance
“…The detection bandwidth can be significantly improved, combined with a broadband photon-pair source [37,38]. The operating wavelength of QFTIR spectroscopy could be extended to the mid-and far-infrared regions by choosing a suitable nonlinear crystal as the photon-pair source [39][40][41][42]. Our method can be applied to a variety of quantum spectroscopy systems, such as those based on a Mach-Zehnder nonlinear interferometer, with minor modifications, and is also applicable for infrared hyperspectral imaging [43].…”
Section: Discussionmentioning
confidence: 99%
“…The detection bandwidth can be significantly improved, combined with a broadband photon-pair source [37,38]. The operating wavelength of QFTIR spectroscopy could be extended to the mid-and far-infrared regions by choosing a suitable nonlinear crystal as the photon-pair source [39][40][41][42]. Our method can be applied to a variety of quantum spectroscopy systems, such as those based on a Mach-Zehnder nonlinear interferometer, with minor modifications, and is also applicable for infrared hyperspectral imaging [43].…”
Section: Discussionmentioning
confidence: 99%
“…The generation and detection of nonclassical light of about 2 µm has good potential in an emerging field of high-sensitivity metrology, especially in gravitational wave detection [1][2][3]. Such long wavelengths can reduce quantum noise and scattering losses in interferometric gravitational wave detectors such as the laser interferometer gravitational wave observatory (LIGO)-Voyager [4].…”
Section: Introductionmentioning
confidence: 99%
“…Mansell et al utilized a combination of a second-harmonic generator and an optical parametric oscillator with two pieces of periodically poled potassium titanyl phosphates (PPKTPs) to generate nonclassical squeezed states of light [1]. Prabhakar et al demonstrated twophoton quantum interference and entanglement at 2.1 µm using Type 0 spontaneous parametric down-conversion (SPDC) in a magnesium oxide-doped periodically poled lithium niobate (MgO:PPLN) [3]. In future studies, the basic requirements of the platform for generating photon pairs in the 2-µm spectral range can be listed as follows: (1) SPDC using the frequency-degenerate Type II extended phase matching (EPM) is desirable for the generation of high spectral purity photon pairs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonclassical states of light, known as any optical field with a nonpositive Glauber–Sudarshan P distribution function, represent useful applications ranging from quantum metrology [ 1 ] to quantum teleportation, [ 2 ] quantum communications and cryptography, [ 3 ] quantum interference and entanglement, [ 4 ] and quantum information processing. [ 5 ] With respect to these applications in modern technology, the question whether a quantum state of light is nonclassical, that is, a state with no classical analogue, has attracted great attention.…”
Section: Introductionmentioning
confidence: 99%